Digital mental health interventions for people with epilepsy: A systematic review. (April 2023) - Lecce, Francesca; Smith, Chelsie R.; Burbach, Frank R.
Abstract: Objective: Although mental health difficulties are common in people with epilepsy, their assessment and treatment are rarely incorporated into routine medical care, with detrimental effects on quality of life. Several barriers to access traditional face to face interventions have been identified, including travel restriction and shortage of appropriately trained mental health clinicians. Digital mental health interventions offer the potential to improve access to mental health treatment. The main aim of the present study is to systematically review the empirical literature to identify what digital mental health interventions for adults, children and young people with epilepsy are currently available, as well as exploring if these interventions are effective in improving mental health and wellbeing. Methods: Searches were conducted using the MEDLINE, PsycINFO, Web of Science and Embase. The reference lists of papers collected were examined in order to identify any further relevant articles cited in peer-reviewed journals. A total of 1490 papers were identified; of these 11 were included in this review. The protocol was registered in the PROSPERO database (CRD42022318658) and the PRISMA 2020 statement was followed. Results: Seven digital interventions were identified. All interventions were based predominantly on CBT and mindfulness techniques and showed promising results in reducing symptoms of depression, with some studies also reporting encouraging results in reducing anxiety and improving satisfaction with life and the quality of life of adults and children and young people with epilepsy. Conclusions: In summary, digital mental health interventions for people with epilepsy seem to be effective and have the potential to improve access to psychological interventions and reach underserved clinical populations. However, further well-powered and methodological rigorous studies are needed to confirm the effect of such interventions for people with epilepsy. Abstract : Assessment and treatment of mental health difficulties in people with epilepsy are rarely incorporated into routine medical care. Digital mental health interventions have the potential to improve access to psychological interventions. We identified five digital mental health interventions for adults and two for children and young people with epilepsy. All interventions are primarily based on CBT and mindfulness and showed encouraging results in improving depression, anxiety and quality of life of people with epilepsy. Further well powered clinical trials are necessary to confirm the effectiveness of such interventions.